2012
DOI: 10.1002/job.1772
|View full text |Cite
|
Sign up to set email alerts
|

Something(s) old and something(s) new: Modeling drivers of global virtual team effectiveness

Abstract: SummaryWe developed and tested a model that bridges existing team effectiveness theory with new ideas aimed at understanding the complexity of multiple team membership and virtuality. Using a sample of 60 global, virtual supply teams from a large multi-national organization, we propose that even for new team configurations, transactive memory systems and preparation activities are critical for effectiveness. We also examined the association between members' percentage of time allocated to a team, team virtuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(162 citation statements)
references
References 104 publications
3
141
1
3
Order By: Relevance
“…This construct was measured using five items adapted from [12] (alpha = 0.897), such as: I always felt free to voice my comments during the meeting and Team members responded to the comments made by others. Coordination is the degree to which team members perceive that they can work together by being able to determine who has what key information and how that information can be stored and accessed [25]. This construct was measured using five items adapted from [25] (alpha = 0.897).…”
Section: (Alpha = 0879) Items Included Statements Such As: I Could mentioning
confidence: 99%
See 1 more Smart Citation
“…This construct was measured using five items adapted from [12] (alpha = 0.897), such as: I always felt free to voice my comments during the meeting and Team members responded to the comments made by others. Coordination is the degree to which team members perceive that they can work together by being able to determine who has what key information and how that information can be stored and accessed [25]. This construct was measured using five items adapted from [25] (alpha = 0.897).…”
Section: (Alpha = 0879) Items Included Statements Such As: I Could mentioning
confidence: 99%
“…Coordination is the degree to which team members perceive that they can work together by being able to determine who has what key information and how that information can be stored and accessed [25]. This construct was measured using five items adapted from [25] (alpha = 0.897). Sample items included: Team members can get the information they need from other members in a timely fashion and We can align our collective knowledge and efforts with task demands.…”
Section: (Alpha = 0879) Items Included Statements Such As: I Could mentioning
confidence: 99%
“…Several studies (Loh & Smyth, 2010;Maynard, Mathieu, Rappand, & Gilson, 2012;Robey, Khoo, & Powers, 2000;Wiedow & Konradt, 2009) suggest that learning to operate within a virtual team is best achieved by participation in virtual teams (Robey et al, 2000). Comba (2011) suggested that teaching "net generation" students (or millennials) merits continued research, that teaching digital competencies is important as online interactions and learning will continue both in higher education and in workplaces now and in the future.…”
Section: Literature Review: Internationalization and Global Virtual Tmentioning
confidence: 99%
“…| 173 Kozlowski, 2014;Maynard, Mathieu, Rapp, & Gilson, 2012), earlier measures based on older definitions are still widely in use in current research literature.…”
Section: Introductionmentioning
confidence: 99%